2016
DOI: 10.2355/isijinternational.isijint-2015-414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydrogen Absorption into Iron by Alternating Current Responses in an Electrochemical Hydrogen Permeation Cell

Abstract: In this paper, hydrogen absorption behavior into iron was investigated by measuring alternating current responses for hydrogen-entry side and hydrogen-withdrawal side in an electrochemical hydrogen permeation cell. Hydrogen absorption efficiency of iron was evaluated as a function of electrode potentials by using both DC and AC components of the current responses. The hydrogen absorption efficiency of iron increased with decreasing cathodic polarization. Furthermore, frequency response characteristics of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the sinusoidal perturbation method, as opposed to the step method, [5][6][7][8][9] sinusoidal perturbation is superimposed on the experimental conditions at the entry-side cell, e.g., perturbation in current density, 5,7 polarization potential, 8 or electrolyte flow rate, 9 while the steady-state condition is maintained at the exit side to detect hydrogen. Sinusoidal perturbation induces sinusoidal signals in the hydrogen mass flux passing through the entry-side interface, which is observed as sinusoidal current at the entry electrode.…”
Section: Need For the Precise Measurement Of Hydrogen Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sinusoidal perturbation method, as opposed to the step method, [5][6][7][8][9] sinusoidal perturbation is superimposed on the experimental conditions at the entry-side cell, e.g., perturbation in current density, 5,7 polarization potential, 8 or electrolyte flow rate, 9 while the steady-state condition is maintained at the exit side to detect hydrogen. Sinusoidal perturbation induces sinusoidal signals in the hydrogen mass flux passing through the entry-side interface, which is observed as sinusoidal current at the entry electrode.…”
Section: Need For the Precise Measurement Of Hydrogen Penetrationmentioning
confidence: 99%
“…The ratio of the exit-current and entry-current amplitudes was used to evaluate hydrogen-absorption efficiency. 8 It was also reported that the AC absorption ratio was more precise than the DC absorption ratio owing to the elimination of the contribution of background current.…”
Section: Need For the Precise Measurement Of Hydrogen Penetrationmentioning
confidence: 99%
“…The slope of − 240 mV/dec corresponds to the potential dependency of i per , which can be derived by assuming that Volmer reaction is the rate-determining step for the hydrogen evolution reaction (HER) on the steel surface. 28,29) Although the plots of i per are scattered, the potential dependency of i per measured in this study is roughly along the line. This result indicates that the hydrogen absorption into steel during the drying of an NaCl droplet is enhanced basically with a negative shift of E corr .…”
Section: Hydrogen Absorption Behavior Of Corroding Steelmentioning
confidence: 65%
“…Many researchers have investigated hydrogen evolution and hydrogen absorption reaction kinetics using the results of Tafel slopes for i entry and i per . 9,26,27) When assuming the reaction rate of hydrogen absorption reaction (Eq. (4)) is much faster than that of the Volmer reaction (Eq.…”
Section: Current Responses To Cathodic Polarizationmentioning
confidence: 99%